Comparison of the efficacy and safety of selective laser trabeculoplasty in cases with primary open‐angle glaucoma and pseudoexfoliative glaucoma. Issue 9 (6th April 2013) - Kara, Necip; Altan, Cigdem; Yuksel, Kemal; Tetikoglu, Mehmet
Abstract: The purpose of this study was to compare the efficacy and safety of selective laser trabeculoplasty (SLT) for patients with primary open‐angle glaucoma (POAG) and pseudoexfoliative glaucoma (PXG). In this retrospective case series, 85 eyes (48 POAG, 37 PXG) of 85 patients were investigated. The medical records of patients who underwent SLT for POAG or PXG were reviewed. The main outcome measures included intraocular pressure (IOP)‐lowering effect and ocular side effects. The mean decrease in IOP differed significantly ( p < 0.001) between eyes with POAG (−4.4 ± 2.1 mmHg) and eyes with PXG (−6.1 ± 3.6 mmHg) at a mean follow‐up period of 1 year. The rate of side effects, such as early IOP spike and uveitis, did not significantly differ between the two groups. In conclusion, SLT has a greater IOP‐lowering effect in PXG compared with POAG.